The Implementation of Problem-Based Learning Model Assisted by PowerPoint Media on Software Material - Engla Wita Rosmawaty Manalu (PT. Mifandi Mandiri Digital, 2023)
The aim of this study is to improve student achievement through the implementation of a problem-based learning model assisted by PowerPoint media among Grade X students of SMA 3 Nasrani Medan. This research employs a classroom action research (CAR) method, which consists of two cycles, each with four stages: planning, action, observation, and reflection. The subjects of the study were 21 students from a Grade X class. Data collection techniques included observation, interviews, tests, and documentation, while data were analyzed using descriptive analysis. The results showed a classical improvement in student achievement. In the pre-cycle stage (before treatment), the average student achievement was 60%. In Cycle I, using the lecture method, it increased to 65%, and in Cycle II, with the implementation of problem-based learning assisted by PowerPoint, it rose significantly to 80%. Based on the results of the study, it can be concluded that the use of a problem-based learning model assisted by PowerPoint media in the first semester can effectively improve student achievement, particularly in learning software-related materials.